Effects of alkyl side chain length of low bandgap naphtho[1, 2‐c:5, 6‐c′]bis[1, 2, 5]thiadiazole‐based copolymers on the optoelectronic properties of polymer solar cells. Issue 18 (7th August 2018) - Tong, Junfeng; An, Lili; Li, Jianfeng; Lv, Jie; Guo, Pengzhi; Li, Liujun; Zhang, Peng; Yang, Chunyan; Xia, Yangjun; Wang, Chenglong
ABSTRACT: Two donor‐π‐acceptor (D‐π‐A) type naphtho[1, 2‐ c :5, 6‐ c ′]bis[1, 2, 5]thiadiazole (NT)‐based conjugated copolymers (CPs), namely, PBDT‐TT‐DTNT‐HD and PBDT‐TT‐DTNT‐OD, containing different side chain length (2‐hexyldecyl, HD and 2‐octyldodecyl, OD) anchoring to thiophene π‐bridge between the two‐dimensional (2D) 5‐((2‐butyloctyl)thieno[3, 2‐ b ]thiophen‐2‐yl)benzo[1, 2‐ b :4, 5‐ b ′]dithiophene (BDT‐TT) unit and NT moiety are developed and fully characterized. The resultant two copolymers exhibited broader absorption in wide range of 300–820 nm and obviously deepened E HOMO of approximately −5.50 eV. The effects of side chain length on film‐forming ability, absorption, energy levels, aggregation, dielectric constant ( ɛ r ), mobility, morphology, and photovoltaic properties are further systematically investigated. It was found that the side chain length had little impact on solution‐processability, absorption, energy levels, and aggregation in CB solution of resultant CPs. However, tinily increasing side chain length promoted to form the more ordered structure of neat polymer film even if the corresponding ɛ r decreased. As a result, the side‐chain‐extended PBDT‐TT‐DTNT‐OD:PC71 BM‐based device achieved 32% increased FF than that of PBDT‐TT‐DTNT‐HD:PC71 BM and thus the PCE was significantly raised from 3.99% to 5.21%, which were benefited from 2 times higher SCLC hole mobility, more favorable phase separation, and improved exciton dissociation. These findings could provide an important and valuable insight by side chain modulation for achieving efficient PSCs. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2059–2071 Abstract : The side chain length had little impact on solution‐processability, absorption, energy levels, and aggregation in chlorobenzene solution. However, the tiny increase of side chain length promoted the formation of the more ordered structure of neat polymer film even if the corresponding dielectric constant decreased. Accordingly, PBDT‐TT‐DTNT‐OD:PC71 BM‐based device achieved a 32% greater increased FF than that of PBDT‐TT‐DTNT‐HD:PC71 BM‐based device and thus the PCE was significantly raised from 3.99% to 5.21%, which benefited from the two times enhanced SCLC hole mobility, more favorable phase separation, and improved exciton dissociation.